Caspase-11 promotes high-fat diet-induced NAFLD by increasing glycolysis, OXPHOS, and pyroptosis in macrophages - Charles Drummer; Fatma Saaoud; Nirag C. Jhala; Ramon Cueto; Yu Sun; Keman Xu; Ying Shao; Yifan Lu; Huimin Shen; Ling Yang; Yan Zhou; Jun Yu; et al. (Frontiers in Immunology, 2023)
IntroductionNon-alcoholic fatty liver disease (NAFLD) has a global prevalence of 25% of the population and is a leading cause of cirrhosis and hepatocellular carcinoma. NAFLD ranges from simple steatosis (non-alcoholic fatty liver) to non-alcoholic steatohepatitis (NASH). Hepatic macrophages, specifically Kupffer cells (KCs) and monocyte-derived macrophages, act as key players in the progression of NAFLD. Caspases are a family of endoproteases that provide critical connections to cell regulatory networks that sense disease risk factors, control inflammation, and mediate inflammatory cell death (pyroptosis). Caspase-11 can cleave gasdermin D (GSDMD) to induce pyroptosis and specifically defends against bacterial pathogens that invade the cytosol. However, it’s still unknown whether high fat diet (HFD)-facilitated gut microbiota-generated cytoplasmic lipopolysaccharides (LPS) activate caspase-11 and promote NAFLD.MethodsTo examine this hypothesis, we performed liver pathological analysis, RNA-seq, FACS, Western blots, Seahorse mitochondrial stress analyses of macrophages and bone marrow transplantation on HFD-induced NAFLD in WT and Casp11–/– mice.Results and DiscussionOur results showed that 1) HFD increases body wight, liver wight, plasma cholesterol levels, liver fat deposition, and NAFLD activity score (NAS score) in wild-type (WT) mice; 2) HFD increases the expression of caspase-11, GSDMD, interleukin-1β, and guanylate-binding proteins in WT mice; 3) Caspase-11 deficiency decreases fat liver deposition and NAS score; 4) Caspase-11 deficiency decreases bone marrow monocyte-derived macrophage (MDM) pyroptosis (inflammatory cell death) and inflammatory monocyte (IM) surface GSDMD expression; 5) Caspase-11 deficiency re-programs liver transcriptomes and reduces HFD-induced NAFLD; 6) Caspase-11 deficiency decreases extracellular acidification rates (glycolysis) and oxidative phosphorylation (OXPHOS) in inflammatory fatty acid palmitic acid-stimulated macrophages, indicating that caspase-11 significantly contributes to maintain dual fuel bioenergetics—glycolysis and OXPHOS for promoting pyroptosis in macrophages. These results provide novel insights on the roles of the caspase-11-GSDMD pathway in promoting hepatic macrophage inflammation and pyroptosis and novel targets for future therapeutic interventions involving the transition of NAFLD to NASH, hyperlipidemia, type II diabetes, metabolic syndrome, metabolically healthy obesity, atherosclerotic cardiovascular diseases, autoimmune diseases, liver transplantation, and hepatic cancers.